Methodology of interaction with the hadith on the day of resurrection (Ahādīth al-Fitan) and its importance in education - Md Yusnan, Mohammad Baihaqi (Faculty of Tarbiyah and Teacher Training of IAIN Padangsidimpuan, 2023)
Believing in the Qiayamat Day is one of the basic proofs of every Muslim's faith. This has been conveyed many times in the hadiths of the Prophet Muhammad SAW which talks about the emergence and state of the Qiayamat Day. Including hadiths that explain the signs and major events that will occur before the Day of Judgment based on the correct scientific discipline. This research aims to explain the methods used by these scholars in understanding and interacting with hadiths regarding Qiayamat day and its urgency in education. The research methodology used is descriptive analysis of the books and writings of authoritative and prominent scholars in the field of hadith. The results of the study state that one way to interact with these hadiths is to ensure that the hadith used as a reference for the incident is authentic in terms of its text (matan) and history (sanad), in its entirety so that understanding each hadith's content is based on the understanding of certified scholars. after carrying out the istiqra' process (collecting and combining various views), and avoiding mistakes in determining the meaning of the hadith to adapt it to events that are or will occur. It is hoped that the findings of this research can correct understanding and ways of interacting with these hadiths so that they can be preserved and perfected and straighten out the understanding of these hadiths among educators and students.